Integrating Patient Safety Discussions with First-Year Doctor of Pharmacy Students in a Skills Lab Course - Kevin T. Fuji; Kimberly A. Galt (MDPI AG, 2024)
The patient safety problem has been well established for over 20 years in the United States (U.S.), and there is a recognized focus on ensuring that health professions' trainees receive explicit education in various patient safety principles and practices. While the literature provides examples of different approaches towards patient safety education for pharmacy students, there are few that focus on first-year pharmacy students. This educational observational study describes the implementation and evaluation of two 20 min patient safety learning activities integrated into a required pharmacy skills lab course. The first learning activity utilized a mock prescription and patient safety checklist that had students identify patient safety problems on the prescription, followed by a group discussion of implications for the patient. The second learning activity used images of common safety problems with a facilitated group discussion to have students identify systems-based solutions to those problems. Our study's findings revealed that students were able to identify basic patient safety problems and safety solutions, although some additional foundational information may be needed, particularly for students who may not have pharmacy work experience. Additional research is needed to continue building a literature base on patient safety education approaches, particularly for first-year pharmacy students.